2020
DOI: 10.5194/tc-2020-57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 14.5 million-year record of East Antarctic Ice Sheet fluctuations from the central Transantarctic Mountains, constrained with cosmogenic <sup>3</sup>He, <sup>10</sup>Be, <sup>21</sup>Ne, and <sup>26</sup>Al

Abstract: Abstract. The distribution of moraines in the Transantarctic Mountains affords direct constraint of past ice-marginal positions of the East Antarctic Ice Sheet (EAIS). Here, we describe glacial-geologic observations and cosmogenic-nuclide exposure ages from Roberts Massif, an ice-free area in the central Transantarctic Mountains. We measured cosmogenic 3He, 10Be, 21Ne, and 26Al in 180 dolerite and sandstone boulders collected from 24 distinct deposits. Our data show that a cold-based EAIS was present, in a con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 77 publications
1
8
1
Order By: Relevance
“…Though our profiles are shallower than profiles from the MDV and Victoria Land in Antarctica (Dickinson et al, 2012;Schiller et al, 2009;Valletta et al, 2015) and Sweden and Alaska in the Arctic (Bierman et al, 2014;Ebert et al, 2012), the soils from these previous studies reached background concentrations of 10 Be within the top 40 cm, which is close to our maximum depth of 30 cm at Thanksgiving Valley. Bennett Platform is most similar to the soil profiles from other regions in Antarctica, as they have decreasing 10 Be concentrations with depth, while The in-situ ages are youngest closer to the glacier at nearly all locations along the Shackleton Glacier (Balter et al, 2020; ICE-D), which is the same trend we observed for the meteoric 10 Be ages. In addition, the in-situ ages and calculated and estimated ages from the Shackleton Glacier region are typically younger at lower elevations and decrease closer to the Ross Ice Shelf (Fig.…”
Section: Calculated and Estimated Exposure Age Validationsupporting
confidence: 76%
See 2 more Smart Citations
“…Though our profiles are shallower than profiles from the MDV and Victoria Land in Antarctica (Dickinson et al, 2012;Schiller et al, 2009;Valletta et al, 2015) and Sweden and Alaska in the Arctic (Bierman et al, 2014;Ebert et al, 2012), the soils from these previous studies reached background concentrations of 10 Be within the top 40 cm, which is close to our maximum depth of 30 cm at Thanksgiving Valley. Bennett Platform is most similar to the soil profiles from other regions in Antarctica, as they have decreasing 10 Be concentrations with depth, while The in-situ ages are youngest closer to the glacier at nearly all locations along the Shackleton Glacier (Balter et al, 2020; ICE-D), which is the same trend we observed for the meteoric 10 Be ages. In addition, the in-situ ages and calculated and estimated ages from the Shackleton Glacier region are typically younger at lower elevations and decrease closer to the Ross Ice Shelf (Fig.…”
Section: Calculated and Estimated Exposure Age Validationsupporting
confidence: 76%
“…2a) and were either deposited or exposed as the documented a large diamictite that is underlain by soils estimated to be a maximum of >14 Myr in age. While this soil age is likely an overestimate given previously published in-situ ages (Balter et al, 2020), the Sirius Group was not observed near the relatively younger RM2-1 soils, with an inheritance-corrected age of 0.14 Myr. We interpret these sparse data to suggest that either the tills were transported from further inland during previous glacial retreat, or that the Sirius Group formed over an extended period of time.…”
Section: Implications For Ice Sheet Dynamicscontrasting
confidence: 55%
See 1 more Smart Citation
“…For 3 He, we targeted pyroxene from the 125-250 micron grain size fraction. Pure pyroxene was obtained using an established HF etching method and 3 He/ 4 He ratios were measured at the Berkeley Geochronology Center noble gas spectrometer following established methods (Bromley et al, 2014;Blard et al, 2015;Balter et al, 2020). We supplemented this data set with eight samples collected prior to the 2016-17 austral summer and those samples were processed with the methods outlined in Oberholzer et al (2003Oberholzer et al ( , 2008Di Nicola et al (2009.…”
mentioning
confidence: 99%
“…As a result, currently exposed soils were overlain and reworked by fluctuations of the Shackleton Glacier and other tributary and alpine glaciers in the region. Exposure ages range from the early Holocene to the Miocene, and generally increase with distance from the coast and distance from the glacier (Balter et al, 2020;Diaz et al, 2020a).…”
Section: Study Sitesmentioning
confidence: 99%